2016
DOI: 10.1136/gutjnl-2016-312012
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sofosbuvir plus simeprevir therapy in Egyptian patients with chronic hepatitis C: a real-world experience

Abstract: A 12-week regimen of simeprevir/sofosbuvir was efficacious and well tolerated by treatment-naïve and treatment-experienced patients with chronic HCV genotype 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 15 publications
6
26
0
Order By: Relevance
“…These results obtained from our study are broadly consistent with the major trends of proven efficacy of such combination therapy in managing HCV as shown in several previous publications [12][13][14][15][16][17][18][19][20]. Our findings were matching with the published results of a Phase III (PLUTO) clinical trial which investigated Simeprevir in combination with sofosbuvir in treatment of naïve and experienced patients with and without compensated cirrhosis in hepatitis C virus genotype 4 infection where this combination achieved SVR rate of 100% among study subjects [12].…”
Section: Discussionsupporting
confidence: 92%
“…These results obtained from our study are broadly consistent with the major trends of proven efficacy of such combination therapy in managing HCV as shown in several previous publications [12][13][14][15][16][17][18][19][20]. Our findings were matching with the published results of a Phase III (PLUTO) clinical trial which investigated Simeprevir in combination with sofosbuvir in treatment of naïve and experienced patients with and without compensated cirrhosis in hepatitis C virus genotype 4 infection where this combination achieved SVR rate of 100% among study subjects [12].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with those of two recent real‐world studies of patients infected with HCV GT4. In treatment‐naïve and treatment‐experienced patients in Egypt, overall SVR12 rates of 96% (558/583) in all patients and 81% (42/52) in METAVIR F4 patients were achieved following 12 weeks of treatment with simeprevir plus sofosbuvir without ribavirin . No patients in this study received ribavirin.…”
Section: Discussionmentioning
confidence: 72%
“…International guidelines have been published to guide treatment decisions and management in order to optimize the results of anti‐HCV therapy . In addition, real‐world studies have confirmed the safety and efficacy of HCV‐DAA combination regimens . Virological failures (VFs), most often posttreatment relapses, are rare.…”
mentioning
confidence: 99%